2019
DOI: 10.1080/12298093.2019.1631121
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compound Produced by Endophytic Fungi Isolated FromPelargonium sidoidesAgainst Selected Bacteria of Clinical Importance

Abstract: Endophytic fungi have the ability to live inside the host plant tissues without causing neither symptoms of diseases/or harm. Opportunistic infections are accountable for majority of the outbreaks, thereby putting a burden on the health system. To investigate and characterize the bioactive compounds for the control of bacteria of clinical importance, extracts from endophytic fungi were isolated from indigenous South African medicinal plants. Extracts from endophytic fungi were isolated from 133 fungal strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The IDZ values are identified based on inhibition zones where the clear zones are less than 10 mm, which are known as low activity, while IDZ values from 10 to 20 mm are considered of medium activity and IDZ values greater than 20 mm are considered to be highly active [ 48 ]. Similarly, Manganyi et al [ 49 ] reported that among 133 endophytic fungi isolated from healthy roots and leaves of medicinal plant Pelargonium sidoides , only the crude extract of sixteen fungal strains showed antibacterial activity against Bacillus cereus, Enterococcus faecium, E. coli , and Enterococcus gallinarum . Moreover, the ethyl acetate extract of five endophytic fungal strains isolated from Nigerian plants Ocimum gratissimum, Newbouldia laevis, and Carica papaya displayed antibacterial activity against Gram-positive and Gram-negative bacteria, while they did not exhibit any antifungal activity against Candida albicans and Aspergillus fumigatus [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The IDZ values are identified based on inhibition zones where the clear zones are less than 10 mm, which are known as low activity, while IDZ values from 10 to 20 mm are considered of medium activity and IDZ values greater than 20 mm are considered to be highly active [ 48 ]. Similarly, Manganyi et al [ 49 ] reported that among 133 endophytic fungi isolated from healthy roots and leaves of medicinal plant Pelargonium sidoides , only the crude extract of sixteen fungal strains showed antibacterial activity against Bacillus cereus, Enterococcus faecium, E. coli , and Enterococcus gallinarum . Moreover, the ethyl acetate extract of five endophytic fungal strains isolated from Nigerian plants Ocimum gratissimum, Newbouldia laevis, and Carica papaya displayed antibacterial activity against Gram-positive and Gram-negative bacteria, while they did not exhibit any antifungal activity against Candida albicans and Aspergillus fumigatus [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…MHE 68 isolated from Pelargonium sidoides yielded cyclodecasiloxane (15) which exhibited a potent broad-spectrum antibacterial activity including drug-resistant enterococcal strains, viz. Enterococcus faecium and Enterococcus gullinarum (Manganyi et al 2019 ). Another endophytic isolate of Alternaria isolated from Schinus terebinthifolius , Alternaria alternata LGMF626 exhibited a potent anti-MRSA activity with an MIC of 18.52 μg/mL of the cell-free extract.…”
Section: Pharmaceutically Active Metabolitesmentioning
confidence: 99%
“…Therefore, the biotechnological application of fungal endophytes in agriculture and industries in the derivation of salient natural plant products became necessary. The discovery of new metabolic compounds from medicinal plants and associated fungi has been documented in several research findings [ 16 , 17 , 18 ]. Currently, Pelargonium sidoides has been recognized as the most invaluable medicinal plant used traditionally in primary health care in South Africa and research on the antibacterial properties of the diverse endophytic fungal extract from Pelargonium sidoides DC has been documented [ 17 ].…”
Section: Introductionmentioning
confidence: 99%